Studies on the Male-responsiveness to the Female Sex Pheromone in Atteva fabriciella Swederus. (Yponomeutidae : Lepidoptera) - Murthy, R. L. N.; Chattoraj, A. N. (Indian Forester, 1978)
The male responsiveness to the female sex-pheromone Atteva fabriciella Swed was studies using both live insects and also crude female pheromone extract in ether. Erection of antennae and curving of abdomen by the male, were taken as standard indication of male responsiveness. The mating behaviour of males with live female insects was observed. The insects of four days old showed maximum pheromone activity (production in the case of females and responsiveness in the case of males). The size of the antennae influences directly the male responsiveness.